2022
DOI: 10.1093/ofid/ofac326
|View full text |Cite
|
Sign up to set email alerts
|

Missed Opportunity: The Unseen Driver for Low Coronavirus Disease 2019 Vaccination Rates in Underserved Patients

Abstract: Background Vaccines against SARS-CoV-2 virus have been available since December 2020. Vaccination rates amongst hospitalized patients at our institution remained low at about 40%, thus we sought to understand the drivers of vaccine hesitancy in our patient population. Methods All unvaccinated adult patients admitted to our hospital were asked to participate in a survey to assess COVID-19 vaccine hesitancy. Updated vaccination… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(7 citation statements)
references
References 7 publications
0
7
0
Order By: Relevance
“…On further screening, 42 articles remained for eligibility assessment after excluding those which were not original studies and not done in slum/underserved communities. The final assessment yielded 24 articles for further analysis [ 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 ].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…On further screening, 42 articles remained for eligibility assessment after excluding those which were not original studies and not done in slum/underserved communities. The final assessment yielded 24 articles for further analysis [ 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 ].…”
Section: Resultsmentioning
confidence: 99%
“…Seventeen (17) studies reported on the factors associated with COVID-19 vaccination (acceptance/hesitancy and uptake), Table 5 . Older age was a strong predictor reported in nine studies, with some reporting a positive association with acceptance and uptake [ 28 , 30 , 35 , 38 , 41 , 42 , 47 ] and a negative association in others [ 27 , 29 ]. High education level and good health literacy were also positive correlates of vaccine acceptance and uptake [ 25 , 29 , 37 , 39 , 42 ], though some studies reported a negative association [ 32 , 38 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations